Utilisation of Business Advice in Small Innovative Firms: the Role of Trust and Tacit Knowledge - Katarzyna Łobacz; Paweł‚ Głodek; Edward Stawasz; Piotr Niedzielski (Entrepreneurial Business and Economics Review, 2016)
Objective: The aim of this paper is to expand the understanding of the influence of trust relationship, as well as tacit knowledge on the process of business advice utilisation in small innovative firms. Research Design & Methods: The analysis is based on empirical research conducted with the use of the explorative approach. The multiple case study methodology was used. Findings: Trust relationships as well as tacit knowledge were identified as factors essential to the process of utilisation of business advice in small innovative firms. It was recognised that the significance of both factors is related not only to the process of advice, but also as a purpose of activities happening prior to advice. They are referred to as the initial phase. Implications & Recommendations: The findings provide implications for further research of the structure of the process of business advice utilisation. It is related to the inclusion of the “initial phase”, as well as to the necessity to include both factors in further research. The paper also provides implications related to the measurement of business advice output, and recommendations on the construction of public policy instruments. Contribution & Value Added: The originality of this work lies in using the process perspective and qualitative methodology in the field of the utilisation of business advice. It extends our understanding of the processes of business advice with regard to trust, as well as the use of tacit knowledge. The original contribution is to add the “initial phase” to the description of the business advice process.